Physics for future presidents : the science behind the headlines - Muller, R. (Richard) (New York : W.W. Norton & Co., 2008)
Learn the science behind the headlines in this work that outlines the tools of terrorists, the dangers of nuclear power, and the reality of global warming.
24. The fruit of the ground -- Comfortable conservation -- Compact fluorescent lights -- Cool colors : when brown paint is white -- Reason for optimism : Rosenfeld's law -- The fizzling population bomb -- Automobile efficiency -- 25. New technologies -- Biofuels -- Concentrating solar -- Safe nukes -- Clean coal -- Carbon credits -- Renewable energy -- Global warming : presidential summary - the buck stops here -- Notes -- Index.
Includes bibliographical references (p. 347-359) and index.
Keywords: Physics -- Social aspects; Science and state; Science in mass media